A Typology of Errors and Myths Perpetuated in Educational Research Textbooks - Anthony J. Onwuegbuzie; Nancy L. Leech (Arizona State University, 2015)
This paper identifies major errors and myths perpetuated by educational research textbooks. The most pervasive errors and myths advanced by methodology textbooks at the following eight phases of the educational research process are described: (a) formulating a research problem/objective; (b) reviewing the literature; (c) developing the research purpose/research question(s) and hypotheses; (d) selecting a research design/method; (e) collecting data; (f) analyzing the data; (g) interpreting/validating the data; and (h) communicating the findings. Second, the implications of these errors and myths are provided. It is shown how research textbooks can be reframed to break down the barriers between quantitative and qualitative research.